Recipe recommendation system / Puteri Nazif Yasir - Yasir, Puteri Nazif (2022)
Food is complicated areas of recommendation technology, but the need for systems to help users to decide on for the suitable recipe is now required. Recipe Recommendation System is application that can display the appropriate recipe to the user by recommending recipes based on the user previous rating. Such as, user like to try the spicy recipes. Hence, the system will suggest a lot of recipe that spicy based on other user ratings. This application also show a different recipe which lead to a various choice of recipe to choose.